Reviews - Lisa Tyler; Fran Claggett; Bruce Novak; Neal Lerner (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Lisa Tyler. Writing and Healing: Toward an Informed Practice. (Charles M. Anderson and Marian M. MacCurdy, eds., 2000). Fran Claggett. Revisioning Writers' Talk: Gender and Culture in Acts of Composing. (Mary Ann Cain, 1995). Bruce Novak. Tomorrow's Children: A Blueprint for Partnership Education in the 21st Century. (Riane Eisler, 2000). Neal Lerner. Stories from the Center: Connecting Narrative and Theory in the Writing Center. (Lynn Craigue Briggs and Meg Woolbright, eds., 2000).